Occurrence and abundance of microplastics in surface water of Songkhla Lagoon - Pradit, Siriporn; Noppradit, Prakrit; Sornplang, Kittiwara; Jitkaew, Preyanuch; Jiwarungrueangkul, Thanakorn; Muenhor, Dudsadee (PeerJ, 2024)
Background Microplastic (MP) pollution is now a global critical issue and has been the subject of considerable worry for multiple various types of habitats, notably in lagoons which are coastal areas connected to the ocean. MPs are of concern, particularly because floating MP in surface water can be ingested by a number of marine organisms. There are several lagoons along Southeast Asia’s coastline, but Songkhla Lagoon is Thailand’s only exit with a rich biodiversity. To date, there has been little research undertaken on MP in this lagoon, so there is a pressing need to learn more about the presence of MP in the lagoon’s water. Methods We investigate MPs in the surface water of Songkhla Lagoon, Thailand. Sampling took place at ten stations in the lagoon during the wet season in December 2022 and the dry season in February 2023. Samples were digested with hydrogen peroxide to remove organic matter followed by density separation using saturated sodium chloride. MPs were visually examined under a stereo microscope to describe and determine the shape, size, and color. Polymer type was identified using a micro Fourier transform infrared (FTIR) spectrometer. Moreover, the in-situ of water quality of the surface water was measured using a multi-parameter probe. A Mann-Whitney U test was performed to investigate the variations in MP levels and water quality parameters between the wet and dry seasons. Correlation analysis (Spearman rho) was used to determine the significance of correlations between MP and water quality (p < 0.05). Results MPs were detected at all ten of the sites sampled. The most abundant MPs were small size class (<500 µm, primarily consisting of fibers). Five types of polymers were seen in surface water, including polyethylene terephthalate, rayon, polypropylene, polyester, and poly (ethylene:propylene). Rayon and polyester were the dominant polymers. Additionally, the most dominant color of MPs in the wet and dry season was black and blue, respectively. The mean contents of MPs in the wet and dry season were 0.43 ± 0.18 and 0.34 ± 0.08 items/L, respectively. The Mann-Whitney U test suggested a significant difference between water quality in the wet and dry seasons (p < 0.05). Correlation analysis (Spearman rho) indicated a negative significant difference relationship between the MPs and the values of total dissolved solid (TDS) in the wet season (r = −0.821, p = <0.05), revealing that the large amounts of MPs may possibly be dispersed within surface water bodies with low TDS concentrations. Based on the overall findings, MP pollution in the surface water of the lagoon is not found to be influenced by the seasonal context. Rivers flowing into the lagoon, especially the U-Taphao River, may be a principal pathway contributing to increased MP pollution loading in the lagoon. The results can be used as baseline data to undertake further research work relevant to sources, fates, distribution, and impacts of MPs in other coastal lagoons.
Keywords: Wetland; Polymer; Lagoon; Plastic debris; Plastic pollution